Evaluation of von Willebrand Factor Antigen as a Prognostic Marker of Major Adverse Cardiac Events in Acute Coronary Syndrome: A Prospective Observational Study - Preethi Yazhini Ravichandran; Krishnaswamy Madhavan (Annals of African Medicine, 2026)
Abstract Background: Acute coronary syndrome (ACS) is a major global cause of morbidity and mortality. Early identification of high-risk patients is crucial for guiding treatment. Von Willebrand factor (VWF) antigen, a marker of endothelial activation and platelet adhesion, plays a role in ACS-related thrombosis. This study evaluated the ability of VWF antigen to predict major adverse cardiovascular events (MACE) and mortality in patients with ACS. Materials and Methods: In this prospective study conducted at a tertiary care hospital, VWF antigen levels were measured using an enzyme-linked immunosorbent assay in 121 patients with ACS. Demographic data, cardiovascular risk factors, clinical presentation, angiographic findings, and treatment were recorded. Patients were monitored for MACE (defined as a composite of heart failure, angina, myocardial infarction, stroke, acute decompensated heart failure, and death) at 4 weeks and 3 months. Results: The mean age of the 121 patients was 58.2 ± 11.8 years; 69.4% were male. At 1 month, MACE occurred in 7.6% of patients, and mortality occurred in 2.5%. At 3 months, MACE occurred in 34.8% of patients and mortality occurred in 3.5%. The median VWF antigen levels were significantly higher in patients with MACE at 3 months than in those without (31.90 [interquartile range (IQR): 27.70–33.50] vs. 12.30 [IQR: 6.00–30.20], P < 0.0001). VWF antigen levels were higher among patients who died, but the difference was not statistically significant ( P = 0.243). A multivariate Cox regression analysis identified VWF antigen levels >26.75 as an independent predictor of MACE at 3 months (adjusted Hazard ratio: 3.82, 95% confidence interval: 1.89–7.72, P < 0.001). ROC analysis for this cutoff demonstrated good predictive performance (AUC: 0.788, sensitivity: 85.0%, specificity: 69.33%). Conclusion: Elevated admission VWF antigen levels were significantly associated with an increased incidence of MACE at 3 months and emerged as an independent predictor of adverse outcomes in patients with ACS. VWF antigen may be a useful biomarker for early risk stratification and identification of high-risk patients who require closer monitoring.